The Effect of Training on Creating Learning Videos Through Kinemaster and Quizizz Applications on Increasing Digital Competence for Madrasah Aliyah (MA) Teachers in Kudus Regency - Masrukhin, Masrukhin; Munajat, Fuad; Anwar, Sahid (Side: Scientific Development Journal, 2024)
Training on making learning videos through kinemaster and quizizz applications for teachers is one of the materials that can improve the digital competence of teachers, in order to improve the quality of learning for students. The development of technology and information communication technology that is developing encourages teachers to be free to blind digital-based technology. This study aims to determine how training in making learning videos through the Kinemaster and Quizizz applications can improve digital competence for MA teachers in Kudus Regency. This research is a research with a Quantitative approach. Data were collected through an online survey questionnaire distributed through a network of MA teachers in Kudus Regency. The sample used was 92 MA teachers in Kudus Regency. After validation, there were 66 respondents who met the criteria for analysis. Statistical analysis using Structural Equation Model (SEM) on Smart PLS. The results showed that the effect of training in making learning videos on improving the digital competence of MA teachers in Kudus Regency. This finding adds to the literature on training to create learning videos for the solution of problems related to teacher digital competence. The suggestion proposed by educational institutions is that it is necessary to measure and monitor the development of teachers' digital competencies which are always developing in accordance with the existing digital era.